Clinical Significance of PD‐L1 Protein Expression in Surgically Resected Primary Lung Adenocarcinoma. Issue 11 (November 2016) - Takada, Kazuki; Okamoto, Tatsuro; Shoji, Fumihiro; Shimokawa, Mototsugu; Akamine, Takaki; Takamori, Shinkichi; Katsura, Masakazu; Suzuki, Yuzo; Fujishita, Takatoshi; Toyokawa, Gouji; Morodomi, Yosuke; Okano, Shinji; et al.
ABSTRACT : Introduction : The clinicopathological features of carcinomas expressing programmed death ligand 1 (PD‐L1) and their associations with common driver mutations, such as mutations in the EGFR gene, in lung adenocarcinoma are not clearly understood. Here, we examined PD‐L1 protein expression in surgically resected primary lung adenocarcinoma and the association of PD‐L1 protein expression with clinicopathological features, EGFR mutation status, and patient outcomes. Methods : The expression of PD‐L1 protein in 417 surgically resected primary lung adenocarcinomas was evaluated by immunohistochemical analysis. The cutoff value for defining PD‐L1 positivity was determined according to the histogram of proportions of PD‐L1–positive cancer cells. Results : Samples from 85 patients (20.4%) and 144 patients (34.5%) were positive for PD‐L1 protein expression according to 5% and 1% PD‐L1 cutoff values, respectively. Fisher's exact tests showed that PD‐L1 positivity was significantly associated with male sex, smoking, higher tumor grade, advanced T status, advanced N status, advanced stage, the presence of pleural and vessel invasions, micropapillary or solid predominant histological subtypes, and wild‐type EGFR . Univariate and multivariate survival analyses revealed that patients with PD‐L1 positivity had poorer prognoses than those without PD‐L1 protein expression at the 1% cutoff value (disease‐free survival p < 0.0001, overall survival p < 0.0001). Conclusions : PD‐L1 protein expression was significantly higher in smoking‐associated adenocarcinoma and in EGFR mutation–negative adenocarcinoma. PD‐L1 protein expression was associated with poor survival in patients with lung adenocarcinoma. The PD‐L1/programmed cell death 1 pathway may contribute to the progression of smoking‐associated tumors in lung adenocarcinoma.